Institute of Metals Division - Precipitation of AgCl in NaCl (AgC1) Solid Solutions (TN) - R. W. Hendricks; R. Baro; J. B. Newkirk (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1964)
STUDIES of the kinetics of precipitation in binary alkali halide systems are of interest from a theoretical point of view, because of the possibility of controlling diffusion rates by additions of aliovalent impurities. This note reports some preliminary results of a study of the kinetics of precipitation of AgCl from supersaturated solid solutions of AgCl in NaCl containing trace amounts of divalent cation impurities. In their study of the system NaC1- AgC1, Stokes and Li1 derived the phase diagram containing a mis-cibility gap with a broad maximum at approximately 170°C. They found that single crystals quenched from above the miscibility gap and aged at various temperatures within the two-phase region gradually turned light blue, then cloudy white, and finally opaque. The rate of transformation depended markedly on the aging temperature. The light-blue color in the early stages of aging was interpreted to be the result of Rayleigh scattering from precipitated particles less than 0.1 µ in diameter. These qualitative observations have been confirmed by us. However, a more precise tool was needed in order to quantitatively follow the growth kinetics of the precipitate particles. Because of the suspected small size of the precipitate particles and for other reasons, small-angle X-ray scattering was thought to be a suitable technique for this study. Small-angle X-ray intensities scattered from powder specimens were recorded on a General Electric XRD-5 diffractometer using the four-slit geometry described by Neynaber, Brammer, and Beeman.2 The slits were 0.08 mm wide by 10.00 mm high. It was found that, with very careful alignment, meaningful data could be obtained to within 3 min from the middle of the direct beam. Chromium radiation (?Ka = 2.29Å) was used in order to spread the scattered intensity to a relatively high angle, as indicated by Eq. [1]. A specimen containing 21.0 at. pet AgCl was prepared by melting analytic reagent-grade AgCl and NaCl under a chlorine atmosphere in a vycor cap-